Transformasi Karawitan Sunda di Kota Bandung (2000–2025): Kajian Sosio-Kultural terhadap Perubahan Praktik Musik - Diah Darmilah (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the transformation of Sundanese gamelan in Bandung City between 2000 and 2025 by highlighting changes in traditional music practices within a socio-cultural context. Sundanese gamelan, as part of cultural heritage, has undergone significant dynamics along with the development of urbanization, globalization, and advances in digital technology. This study uses a qualitative approach with descriptive-analytical methods, through literature studies, observations, and interviews with artists and gamelan communities in Bandung City. The results show that the transformation of Sundanese gamelan is reflected in several aspects, namely changes in performance forms, innovations in instruments and arrangements, and a shift in function from being ritualistic and communal to being more flexible, including as a medium of entertainment and a cultural commodity. In addition, the presence of digital media has expanded the space for expression and distribution of Sundanese gamelan, although it also poses challenges to the authenticity and preservation of traditional values. Socio-culturally, this transformation demonstrates a process of adaptation and negotiation of Sundanese cultural identity amidst the current of modernization. Sundanese gamelan not only survives as a tradition, but also develops as a dynamic cultural practice that is relevant to the current context. Thus, this study confirms that the transformation of Sundanese gamelan is part of a cultural strategy in maintaining the sustainability of cultural heritage amidst ongoing social change.